Kontestasi Sistem Ekonomi Islam dan Konvensional - Rusdin Muhalling (Institut Agama Islam Negeri Kendari, 2017)
Economic Thought emerged since the presence of human beings on earth, This thinking is areaction to the empirical dynamics in all aspects of human life. Fairness is a recognition andequal treatment between rights and obligations. Based on ethical awareness, humans arerequired to demand not just rights and to forget obligations. If it only demands rights andcarries obligations, then its attitudes and actions will tend to lead to extortion andenslavement of others.Conversely, if a human only performs obligations and forgets to claim his rights, it willbe easily blackmailed by others. For example, employer and employer relations, traders andbuyers, etc., then it is necessary to understand a fair understanding, so that each knows itsrole where the rights and where the obligations. That way, they can put themselves in theright position. If it can be understood together then the so-called harmony and harmony willbe created. Although many theories hold that injustice is the logical consequence of a systemthat applies whether economically, socially, or politically in a society.